HOTS-Oriented Student Worksheets with Blended Learning: Improving Students' Science Process Skills - Nurulsari, Novinta; Nisa', Khairun; Viyanti, Viyanti; Yassine, Brahimi (CV FOUNDAE, 2023)
Today's education must meet the needs of 21st-century learning and developments in the digital age. HOTS and science process skills must be trained to carry out scientific investigations. This experimental research aims to identify the improvement of students' science process skills affected by HOTS-oriented student worksheets through blended learning conducted in one of the high schools in Pringsewu District, Lampung Province. The subjects of this study were students of class X SMA Negeri 2 Pringsewu, with a population of 180 people. The research sample was selected using a purposive sampling technique so that class MIPA 2 was obtained as an experimental class with a total of 29 students and MIPA 4 class as a control class with a total of 31 students. The research method used was a non-equivalent control group design which aims to look for the effect of a causal relationship between two factors. The data collection technique used was a pretest and posttest design using a science process skills instrument. The n-gain results show an increase in 5 indicators of students' science process skills, where the increase occurs in the medium category. The results showed an increase after using HOTS-Oriented Student Worksheets (SW) on impulse-momentum material through blended learning to improve students' science process skills.